2012
DOI: 10.3346/jkms.2012.27.11.1398
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Irritable Bowel Syndrome, Worry and Stress in Adolescent Girls

Abstract: The aim of this study is to investigate prevalence of irritable bowel syndrome (IBS) among adolescents and difference in worry and stress between normal and IBS groups. Questionnaire survey was conducted at a girl's middle and high school. Students from seventh to eleventh grade participated in the examination on Rome II criteria, lifestyle and dietary habits. Worry and stress were measured with the Korean version Penn State Worry Questionnaire-Children and the Korean version Brief Encounter Psychosocial Instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 29 publications
6
44
0
3
Order By: Relevance
“…Similar results were obtained among nursing students from Korea (22) and university students from Germany (25). Similarly, studies among the general populations also reported strong associations between female gender and IBS (21,23,(26)(27)(28)(29). Results from an Iranian systematic review showed that more than one-half of the reviewed researchers found that IBS was significantly associated with female gender (26).…”
Section: Risk Factors  Gendermentioning
confidence: 99%
“…Similar results were obtained among nursing students from Korea (22) and university students from Germany (25). Similarly, studies among the general populations also reported strong associations between female gender and IBS (21,23,(26)(27)(28)(29). Results from an Iranian systematic review showed that more than one-half of the reviewed researchers found that IBS was significantly associated with female gender (26).…”
Section: Risk Factors  Gendermentioning
confidence: 99%
“…IBS is common in Western countries, where the incidence is up to 20%. In recent years, the morbidity in Asian countries has been rising year by year, and has now nearly reached that of Western countries (Zhong and Hou, 2012;Song et al, 2012;Omagari et al, 2013). Without biological markers, the diagnosis of IBS depends mainly on the patient's symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Psychiatric disorders include panic disorder, generalized anxiety disorder, mood disorders, depression and post-traumatic stress disorder (1,28). Although there is currently no convincing evidence that psychological factors play a role in the onset and/or progression of IBS (2,12), in cases of anxiety disorders, hyperactivity of neurotransmitters, such as serotonin, may cause abdominal susceptibility or motility disorders in the gastrointestinal system (brain-gut interactions) (3,26,28). There are limitations worth noting in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Brain-gut disorders and psychiatric and social factors have also been recognized to be possible pathologic mechanisms of IBS. Psychiatric factors reported to worsen IBS include anxiety, somatization disorder and depression (3). Comprehensive studies on the associations between the mental, physical, dietary and/or nutritional status and IBS in young Japanese women, however, are few.…”
Section: Classificationmentioning
confidence: 99%
See 1 more Smart Citation